Analysis of Korean and global indicators and policy proposal for sustainable development goals - MIN, Jungeun (KDI School, 2022)
Climate change has emerged as a serious challenge for South Korea in terms of sustainable water management and is demanding changes in the water management policies. Since the severe drought that occurred in Chungcheongnam-do and Gangwon-do in 2016, I learned that Korea is no longer immune to drought. Furthermore, I recognized the need for a sustainable water management policy to achieve the UN SDG, which aims to ensure access to safe water for everyone. In this context, this study analyzes the results of recent studies on sustainable development goals and the Goal 6 Target established by the UN. In addition, it compares and analyzes SDGs global indicators and Korea's K-SDGs indicators in the water sector. Each indicator reviews the level of implementation in South Korea and presents complementary indicators suitable for the current situation. In conclusion, in order to improve areas with low SDGs performance, this study proposes a policy direction focusing on water infrastructure public projects in South Korea.
Thesis(Master) -- KDI School: Master of Public Management, 2022
Keywords: Sustainable development; Water resources development